-5-2x-9=-4

Simple and best practice solution for -5-2x-9=-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5-2x-9=-4 equation:


Simplifying
-5 + -2x + -9 = -4

Reorder the terms:
-5 + -9 + -2x = -4

Combine like terms: -5 + -9 = -14
-14 + -2x = -4

Solving
-14 + -2x = -4

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '14' to each side of the equation.
-14 + 14 + -2x = -4 + 14

Combine like terms: -14 + 14 = 0
0 + -2x = -4 + 14
-2x = -4 + 14

Combine like terms: -4 + 14 = 10
-2x = 10

Divide each side by '-2'.
x = -5

Simplifying
x = -5

See similar equations:

| -2(-4+8q)= | | 3(x+1)=1/81 | | 33=-11a+88 | | (-2+sqrt-8)+(5-sqrt-50)= | | 7p-3q-5q= | | 9+6x^2+x^3=0 | | X^2=x^2-6x | | 12.687*10-4= | | -2x+27=-41 | | -13=12b-b-10 | | -15m=300 | | -17a=289 | | 3a+1=-3*6(a-1) | | 2w-0.4=1+1.18w | | 450-90m=-270 | | 3x+8=9x+12 | | 26-13x=-52 | | 553/48x=265 | | -7=7/8k | | 1.5x+2=20 | | (3c-5)(3c-5)= | | -4(y+2)-6y= | | -5x+47=-31 | | -2(y+6)=y+3-(-2y) | | -180=2x+7(5x-12) | | 2x-6=3x+1-x | | -5h=85 | | 11-(-8x)+5x-(-10)= | | -3a+5+4a=10-26+5 | | 4-28x=-28x-40 | | 7(-1-3k)= | | 5(3x+6y)+4(2x-9y)= |

Equations solver categories